2014
DOI: 10.3325/cmj.2014.55.228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high fat diet, ovariectomy, and physical activity on leptin receptor expression in rat brain and white fat tissue

Abstract: AimTo evaluate in a rat animal model whether ovariectomy, high fat diet (HFD), and physical activity in the form of running affect leptin receptor (Ob-R) distribution in the brain and white fat tissue compared to sham (Sh) surgery, standard diet (StD), and sedentary conditions.MethodsThe study included 48 female laboratory Wistar rats (4 weeks old). Following eight weeks of feeding with standard or HFD, rats were subjected to either OVX or Sh surgery. After surgery, all animals continued StD or HFD for the nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Altogether, the results indicated that the consumption of this 45%-lard diet for 12 weeks had mild effects, perhaps due to the caloric and lipidic density of the diet as well as to the period of diet exposure. In agreement with this suggestion, other authors reported that the intake of a 45% lard-rich diet for 8 weeks by female rats failed to increase body fat percentage 35 , while a 62%-lard diet for 50 weeks doubled the body weight gain of female rats 36 . In male mice, the intake of a 60%-lard diet 16 weeks induced pronounced changes in body adiposity, glucose homeostasis, and leptinemia 37 .…”
Section: Discussionsupporting
confidence: 63%
“…Altogether, the results indicated that the consumption of this 45%-lard diet for 12 weeks had mild effects, perhaps due to the caloric and lipidic density of the diet as well as to the period of diet exposure. In agreement with this suggestion, other authors reported that the intake of a 45% lard-rich diet for 8 weeks by female rats failed to increase body fat percentage 35 , while a 62%-lard diet for 50 weeks doubled the body weight gain of female rats 36 . In male mice, the intake of a 60%-lard diet 16 weeks induced pronounced changes in body adiposity, glucose homeostasis, and leptinemia 37 .…”
Section: Discussionsupporting
confidence: 63%
“…A study conducted by Blažetić et al ( 69 ) using an animal model revealed increased distribution of leptin receptors (Ob-R) in the lateral hypothalamic nucleus, but without effect on the arcuate nucleus resulting from a fat-rich diet. This way, in obesity, despite the high concentration of circulating leptin and possible increase in the number of receptors in the brain, leptin does not induce the expected response of decreased intake and increased energy expenditure.…”
Section: Adipose Tissue As An Endocrine Organmentioning
confidence: 99%
“…They have excessive WAT in the body and it secretes leptin in the blood; however, the appetite center does not recognize leptin and shows resistance to leptin. Therefore, leptin administration to obese rats and humans has elicited small effects on fat mass and appetite due to leptin resistance [2,53,148] . Likewise, many neuropeptides located in hypothalamic nuclei transmit related anorexigenic or orexigenic signals [104,146] .…”
Section: Dm and Central Nervous Systemmentioning
confidence: 99%
“…Hence, uncontrolled chronic obese condition can be a critical factor in the development of T2DM, and it also acts as an agent that affects normal brain functions. Recently many studies have shown the positive effects of regular physical activity on improving complications caused by DM, and hence regular physical activity intervention is regarded as a promising adjuvant therapy [7,37,[51][52][53][54][55][56][57][58][59][60][61][62] . Exercise can affect various physical environments and has decisive effects on improving brain functions for a better quality of life [7,[59][60][61][63][64][65][66][67][68][69][70][71][72] .…”
Section: Introductionmentioning
confidence: 99%